PENGARUH PENGUNGKAPAN CSR TERHADAP KINERJA PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013,2015 dan 2017) - Tukma Ida Putri Harahap; Aditya Septiani (Diponegoro Journal of Accounting, 2019)
ABSTRACTThis study aims to determine how the effect of the change in total corporate social responsibility disclosure (CSRD) for the previous period to the change in financial and market performance of corporate for the next period. In this study the independent variables change in total CSR disclosure used the standard by Global Reporting Initiatives namely economical impact, employment, environtment, product responsibilty, Social, and human rigts. Change in total corporate social responsibility disclosure (CSRD) will be tested its effect on the dependent variables change in financial and market performance which is proxied by change in Return on Asset (ROA), change in Earning Per Share (EPS) and change in Market Price (MP). This study also used control variables, namely change in research and development expenditure, change in financial leverage, and market capitalisation. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2013,2015, and 2017 with total sample were 94 companies which determined by purposive sampling method. Data analysis in this research carried out by using the classical assumption, whereas hypothesis testing carried out by using linear regression namely Ordinary Least Squares method (OLS) . The results of this study show that change in CSR Disclosure in the previous period has positive and significant effect on the change in corporate’s financial and market performance in the next period. Menwhile control variable doesn’t has an effect on the change in corporate’s financial and market performance in the next period.